Peran Kepuasan Kerja Dalam Memediasi Kualitas Pelayanan Dan Fasilitas Terhadap Kinerja Tenaga Kesehatan Pada Klinik Umum Di Kota Serang - Veriana, Ice; Suparmoko, Muhammad; Mukhlis, Ahmad (STIE AMKOP, 2024)
Clinics as one of the public service institutions in the health sector require several attentions such as service quality, facilities and performance of health workers. To improve services to patients and other related environments, this research specifically aims to identify the influence of patient satisfaction in mediating the quality of services and facilities on the performance of Health Personnel (NAKES) at public clinics in the city of Serang. Human resources are one of the most crucial components in a service at a health clinic, so it is appropriate for health clinics to carry out a mechanism for maintaining human resources by paying attention to service quality and evaluating performance in order to obtain quality health clinic services. This research used a quantitative method with structural equation modeling partial least squares (SEM-PLS) analysis with a sample of 120 patients and families of public clinic patients in Serang City. The research results prove that from the coefficient column there is a significant positive influence between Service Quality and Job Satisfaction, there is a significant positive influence between Facilities and Job Satisfaction, and there is a significant positive influence between Job Satisfaction and Performance. There is a significant positive influence of Service Quality on Performance through the mediation of Job Satisfaction. There is a significant positive influence of Facilities on Performance through the mediation of Job Satisfaction. Keywords: Clinics, public service, health sector, service quality, facilities, performance, health workers